The Role of the Prosecutor in the System of Criminal Prosecution in Russia - YUSUPOV, Magomedgadzhi Yu; MAGOMEDOV, Bagavdin M.; DZHAMALOVA, Bika B.; MAGOMEDOV, Guseyn B.; AKUTAEV, Rasul M. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The urgency of the problem studied is caused by the need for further understanding of the constitutional and legal concept of the prosecutor's office, primarily in the context of its criminal prosecution function. The purpose of the paper is to formulate proposals for improving the legal status of the prosecutor in the criminal process of Russia in the current conditions of the ongoing search for the optimal model of the criminal process. The research was conducted using formal-logical, historical-legal, system-structural and comparative-legal methods, which allowed formulating proposals for improving the legal status of the prosecutor in the system of criminal prosecution. The paper substantiates the opinion that the weakening of the prosecutor's role in the criminal prosecution as a result of the 2007 reform destroys the conceptual basis of the criminal process that has been developed in the legal tradition of Russia and in the world practice and creates difficulties for the prosecutor in presenting and maintaining by him a state charge in the Court. Proposals have been formulated to expand the powers of the prosecutor in pre-trial criminal prosecution. The proposals expressed in the paper can be useful in the ongoing reform of the criminal process in Russia. The results of the research are of some interest to the faculty, post-graduates and students of law universities and faculties.